Peningkatan Kapasitas Aparatur BAPPEDA Kabupaten Pringsewu dalam Penulisan Jurnal Ilmiah Litbang melalui Pendampingan dan Asistensi - Aminudin, Nur; Wantoro, Agus (Universitas Tanjungpura, 2026)
The capacity of local government officers in writing scientific journal articles based on Research and Development (R&D) outputs remains relatively low, resulting in limited publication of regional research findings. This issue is also experienced by the Regional Development Planning Agency (BAPPEDA) of Pringsewu Regency, where most R&D outputs are still presented as internal reports rather than publishable journal articles. This Community Service Program (PKM) aims to enhance the knowledge and skills of BAPPEDA officers in scientific journal writing and to produce draft journal articles based on regional R&D studies. The methodology employed includes a scientific writing workshop, direct mentoring in manuscript preparation, and intensive assistance in reviewing participants’ draft articles. The results indicate a significant improvement in participants’ understanding of journal article structure, abstract writing, research methodology application, and the use of proper citation and references. In addition, participants were able to produce initial draft journal articles derived from their existing R&D reports. This PKM activity has a positive impact on strengthening officers’ capacity and fostering a scientific writing culture within BAPPEDA. In conclusion, the mentoring and direct assistance approach is effective in addressing partners’ problems and supporting the improvement of regional R&D scientific publication quality.